2017
DOI: 10.4103/njms.njms_84_16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of arthrocentesis versus arthrocentesis with sodium hyaluronic acid in temporomandibular joint osteoarthritis: A comparison

Abstract: Introduction:Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative disease characterized by deterioration of articular tissue with concomitant osseous changes in the condyle and/or articular eminence, joint positive for TMJ noise with jaw movement or function, crepitus detected on palpation on opening, closing, right/left lateral, or protrusive movement. Hyaluronic acid (HA) is a polysaccharide of the family of glycosaminoglycans. HA has been shown to improve and restore normal lubrication in joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
2
31
0
5
Order By: Relevance
“…Although this study didn't use arthrocentesis but it casts a shadow on the minimal potential of hyaluronic acid in treatment of TMJ/OA. Likewise, Gurung, et al [29] in 2017 obtained similar results where the mild reparative ability of hyaluronic acid on the osteoarthritic degeneration was manifested using CBCT .Similar results were attained by Sun, et al [49] where the hyaluronate injection in the osteoarthritic joints improved the clinical symptoms but it failed to quit the progression of joint degeneration.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although this study didn't use arthrocentesis but it casts a shadow on the minimal potential of hyaluronic acid in treatment of TMJ/OA. Likewise, Gurung, et al [29] in 2017 obtained similar results where the mild reparative ability of hyaluronic acid on the osteoarthritic degeneration was manifested using CBCT .Similar results were attained by Sun, et al [49] where the hyaluronate injection in the osteoarthritic joints improved the clinical symptoms but it failed to quit the progression of joint degeneration.…”
Section: Discussionsupporting
confidence: 54%
“…Gurung et al [29] , in 2017 conducted a study comparing the effect of arthrocentesis alone and coupled with for 3 -5 consecutive weeks in contrast to our single technique. Yet, Hegab, et al [33] in 2015 reported the short term effectiveness of HA on symptoms associated with TMJ/OA inspite of repeating the technique for three consecutive weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not distinguish between muscle and joint pain, in a typically synthetic approach that dominates the research on the effectiveness of TMD treatment with joint rinsing and viscosupplementation. The study by Gurung et al [25] on the effectiveness of intra-articular HA injections as an additional procedure performed after rinsing the joint cavity is no exception. In the studied group of 10 patients, the pain intensity expressed on the VAS scale decreased from 5.9 to 1.3, i.e., by 78%, compared to a 56% pain reduction following joint rinsing only.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of combining joint rinsing with HA viscosupplementation should also be considered. In a unique study by Gurung et al [25], the highest efficacy in improving chewing function by using this combination of therapies was demonstrated. The amplitude of mandibular opening in the group of patients treated with a combination of joint rinsing and viscosupplementation was 13% higher than in the control group treated with joint rinsing alone.…”
Section: Authors (Date Ofmentioning
confidence: 98%
“…Treatment with arthrocentesis is very effective and the results are comparable to arthroscopy or arthrotomy. The success of arthrocentesis is indicated in 70-80 % of cases, which is comparable to arthroscopy (more than an 80 % success rate) (9,11,15,25,27).…”
Section: Discussionmentioning
confidence: 87%